Data mining and machine learning: an Overview of Classifiers - Haghighi, Mehri (Ciência e Natura, 2015)
At the same time of information age, digital revolution has made necessary using some of technologies to analyze most of essential information. Data mining is a technique to make sense to the available data. The aim of data mining is extracting the information from a vast volume of data and transforming them into a comprehensible form for human. For this purpose, machine learning methods are used to classify data. In this study, we discuss six popular and useful classifiers in the data mining process.